The Aetiology of Delay to Commencement of Adjuvant Chemotherapy following Colorectal Resection. (17th March 2014) - Simpson, G. S.; Smith, R.; Sutton, P.; Shekouh, A.; McFaul, C.; Johnson, M.; Vimalachandran, D.
Abstract : Purpose . Timely administration of adjuvant chemotherapy following colorectal resection is associated with improved outcome. We aim to assess the factors which are associated with delay to adjuvant chemotherapy in patients who underwent colorectal resection as part of an enhanced recovery protocol. Method . A univariate and multivariate analysis of patient data collected as part of a prospectively maintained database of colorectal cancer patients between 2007 and 2012. Results . 166 patients underwent colorectal resection followed by adjuvant chemotherapy. Median postoperative hospital stay was 6 days, and time to commencement of adjuvant chemotherapy was 50 days. Longer inpatient stay correlated with increased time to adjuvant chemotherapy (P = 0.05 ). Factors found to be independently associated with duration of hospital stay and time to commencement of adjuvant chemotherapy included stoma formation (P = 0.032 ), anastaomotic leak (P = 0.027 ), and preoperative albumin (P = 0.027 ). The use of laparoscopic surgery was associated with shorter time to adjuvant chemotherapy but did not reach significance (P = 0.143 ). Conclusion . A number of independent variables associated with delay to adjuvant therapy previously not described have been identified. Further work may be required to elucidate the effect that these variables have on long-term outcome.